Associations between stress disorders and cardiovascular disease events in the Danish population. Issue 12 (14th December 2015) - Gradus, Jaimie L; Farkas, Dóra Körmendiné; Svensson, Elisabeth; Ehrenstein, Vera; Lash, Timothy L; Milstein, Arnold; Adler, Nancy; Sørensen, Henrik Toft
Abstract : Objectives: Post-traumatic stress disorder (PTSD) is a well-documented risk factor for cardiovascular disease (CVD). However, it is unknown whether another common stress disorder—adjustment disorder—is also associated with an increased risk of CVD and whether gender modifies these associations. The aim of this study was to examine the overall and gender-stratified associations between PTSD and adjustment disorder and 4 CVD events. Design: Prospective cohort study utilising Danish national registry data. Setting: The general population of Denmark. Participants: PTSD (n=4724) and adjustment disorder (n=64 855) cohorts compared with the general population of Denmark from 1995 to 2011. Primary outcome measures: CVD events including myocardial infarction (MI), stroke, ischaemic stroke and venous thromboembolism (VTE). Standardised incidence rates and 95% CIs were calculated. Results: Associations were found between PTSD and all 4 CVD events ranging from 1.5 (95% CI 1.1 to 1.9) for MI to 2.1 (95% CI 1.7 to 2.7) for VTE. Associations that were similar in magnitude were also found for adjustment disorder and all 4 CVD events: 1.5 (95% CI 1.4 to 1.6) for MI to 1.9 (95% CI 1.8 to 2.0) for VTE. No gender differences were noted. Conclusions: By expanding beyond PTSD and examining a second stress disorder—adjustment disorder—this study provides evidence that stress-related psychopathology is associated with CVD events. Further, limited evidence of gender differences in associations for either of the stress disorders and CVD was found.